Evolución de las causas de defunción en una ciudad de África occidental: Banjul, 1942-1997 - Marianne A.B. van der Sande; Hazel M. Inskip; Kebba O. Jaiteh; Nicholas P. Maine; Gijs E.L. Walraven; Andrew J. Hall; Keith P.W.J. McAdam
OBJECTIVE: To determine trends in the causes of death in a West African town. Mortality caused by infectious diseases is reported to be declining while degenerative and man-made mortality factors are increasingly significant. Most mortality analyses for sub-Saharan Africa have involved extrapolation and have not been derived from community-based data. METHODS: Historical data on causes of death coded by physicians were analysed for the urban population of Banjul for the period 1942-97. As the calculation of rates is not possible in the absence of a reliable population denominator, age-standardized proportional mortality ratios (PMRs) for men and women by major groups of causes of death were calculated, using the 1942-49 data for reference purposes. FINDINGS: Most deaths were attributable to communicable diseases. There was a shift in proportional mortality over the study period: the contribution of communicable diseases declined and that of noncommunicable diseases and injuries increased. These trends were more marked among men than women. CONCLUSIONS: The data illustrate that while noncommunicable diseases and injuries are emerging as important contributors to mortality in sub-Saharan Africa, communicable diseases remain significant causes of mortality and should not be neglected.